Analisis Sistem Informasi Akuntansi Persediaan Obat-Obatan (Studi Kasus pada UPT Puskesmas Ambarawa) - Denti Yuliani; Sunarmi Sunarmi (Departement of Mathematics Education, 2023)
This study aims to determine the application of the drug inventory accounting information system at the UPT Puskesmas Ambarawa. The type of research used is descriptive quantitative. The data collection techniques used in this study were observation, interviews, and documentation. While the analysis techniques used are data reduction, data presentation, and conclusions. From the results of the studyi it can be concluded that the application of the drug inventory accounting information system at the Ambarawa Health Center has not been effective and efficient, because there are still errors in recording drug supplies. Inventory recording still uses micosoft excel has not used special software for recording drug inventory so that the use of the drug recording information system at UPT Puskesmas Ambarawa has not run effectively and efficiently.